2007
DOI: 10.1002/ejoc.200601052
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Route to a Bromo‐Cyano‐Substituted Azulene and Its Exploitation in the Construction of an Acetylenic Scaffold

Abstract: A novel route to functionalized azulenes is devised from a dihydroazulene precursor. Thus, bromination of 1,1-dicyano-2-phenyl-1,8a-dihydroazulene followed by heating in the presence of bromide ions provides an efficient way to generate 3-bromo-1-cyano-2-phenylazulene. Formation of this somewhat unexpected product was confirmed by X-ray crystallographic analysis. It undergoes a palladium-catalyzed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 23 publications
(17 reference statements)
1
25
0
Order By: Relevance
“…We have recently reported that bromination of 1 occurs selectively at the 7,8-positions in quantitative yield to provide the dibromide 5 (confirmed by X-ray crystal structure analysis, Figure 1) as a pair of enantiomers. [4] In fact, treatment with two molar equivalents of bromine selectively furnished the tetrabromide 6, while treatment with three (or more) equivalents furnished the hexabromide 7 as confirmed by X-ray crystal structure analysis (Figure 1). Treating dibromide 5 with ca.…”
Section: Resultsmentioning
confidence: 76%
“…We have recently reported that bromination of 1 occurs selectively at the 7,8-positions in quantitative yield to provide the dibromide 5 (confirmed by X-ray crystal structure analysis, Figure 1) as a pair of enantiomers. [4] In fact, treatment with two molar equivalents of bromine selectively furnished the tetrabromide 6, while treatment with three (or more) equivalents furnished the hexabromide 7 as confirmed by X-ray crystal structure analysis (Figure 1). Treating dibromide 5 with ca.…”
Section: Resultsmentioning
confidence: 76%
“…The synthesis starts with selective bromination of parent unsubstituted DHA 4 to give dibromide 5, [8] followed by elimination of HBr to give the 7-bromo DHA 6.…”
Section: Resultsmentioning
confidence: 99%
“…It was instead possible to introduce another bromine in position 7 to give a 3,7-dibromo-substituted DHA through a bromination/elimination protocol, which had already been established for DHA 1 itself (vide infra, Section 4). 31 …”
Section: Reactivity and Functionalization Of The Five-membered Ring Omentioning
confidence: 99%
“…[31][32][33][34] It consists of a sequential bromination/elimination protocol, which furnished selectively the 7-bromo DHA 17 starting from DHA 1 (Scheme 7). Addition of up to three molar equivalents of elemental bromine was possible in the first step (Scheme 8).…”
Section: Reactivity and Functionalization Of The Seven-membered Ring mentioning
confidence: 99%
See 1 more Smart Citation